Liquid Metal Grid Patterned Thin Film Devices Toward Absorption-Dominant and Strain-Tunable Electromagnetic Interference Shielding - Wei, Yuwen; Bhuyan, Priyanuj; Kwon, Suk Jin; Kim, Sihyun; Bae, Yejin; Singh, Mukesh; Tran, Duy Thanh; Ha, Minjeong; Jeong, Kwang‑Un; Ma, Xing; Park, Byeongjin; Park, Sungjune (Nano-Micro Letters, 2024)
The demand of high-performance thin-film-shaped deformable electromagnetic interference (EMI) shielding devices is increasing for the next generation of wearable and miniaturized soft electronics. Although highly reflective conductive materials can effectively shield EMI, they prevent deformation of the devices owing to rigidity and generate secondary electromagnetic pollution simultaneously. Herein, soft and stretchable EMI shielding thin film devices with absorption-dominant EMI shielding behavior is presented. The devices consist of liquid metal (LM) layer and LM grid-patterned layer separated by a thin elastomeric film, fabricated by leveraging superior adhesion of aerosol-deposited LM on elastomer. The devices demonstrate high electromagnetic shielding effectiveness (SE) (SET of up to 75 dB) with low reflectance (SER of 1.5 dB at the resonant frequency) owing to EMI absorption induced by multiple internal reflection generated in the LM grid architectures. Remarkably, the excellent stretchability of the LM-based devices facilitates tunable EMI shielding abilities through grid space adjustment upon strain (resonant frequency shift from 81.3 to 71.3 GHz @ 33% strain) and is also capable of retaining shielding effectiveness even after multiple strain cycles. This newly explored device presents an advanced paradigm for powerful EMI shielding performance for next-generation smart electronics. Highlights: 1 Multiple internal reflection-based absorption-dominant stretchable electromagnetic shielding thin film by incorporating liquid metal grid structure is developed. 2 The device demonstrates high electromagnetic shielding effectiveness (SE) (SET of up to 75 dB) with low reflectance (SER of 1.5 dB at the resonant frequency). 3 The shielding properties of the device can be tuned by adjusting the liquid metal patterned grid spaces upon strain.